Pests won't stop at the borders - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Existing plant protection regulations in the Caribbean are not only outdated but suffer from a lack of technical backup. That explains why over the last 25 years these islands have been menaced by many pests that have been introduced from other...